Microstructural characteristics of chronic infarct segments assessed using diffusion tensor imaging. (13th July 2021) - Das, A; Kelly, C; Teh, I; Stoeck, C; Kozerke, S; Chowdhary, A; Jex, N; Thiranavukarasu, S; Sharrack, N; Ben-Arzi, H; Aldred, M; Greenwood, JP; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Background: The microstructural changes following myocardial infarction (MI) can be characterised in-vivo with cardiac diffusion tensor imaging (cDTI) imaging, using mean diffusivity (MD), fractional anisotropy (FA), secondary eigenvector angle (E2A) and helix angle (HA) maps. In this study, we use cDTI to explore the microstructural differences between subendocardial and transmural chronic infarct segments. Method: Twenty STEMI patients (15 men, 5 women, mean age 59) underwent 3T CMR scan at 3 months following presentation (mean interval 107 ± 18 days). Scan protocol included: second order motion compensated (M012) free-breathing spin echo DTI (3 slices, 18 diffusion directions at b-values 100s/mm2[3], 200s/mm2[3] and 500s/mm2[12], acquired resolution was 2.20x2.27x8mm3; cine gradient echo and LGE imaging. Average MD, FA, E2A and HA parameters were calculated on a 16-AHA-segmental level. HA maps were described by dividing values into left-handed HA (LHM, -90° < HA < -30°), circumferential HA (CM, -30° < HA < 30°), and right-handed HA (RHM, 30° < HA < 90°) and reported as relative proportions. Infarct segments were identified using LGE; patients were categorised according to the maximal transmurality of their infarct segments, into subendocardial (<50% LGE) or transmural (>50% LGE) MI. Results: DTI acquisition was successful in all patients (acquisition time 13 ± 5mins). Ten patients had transmural MI. The results are shown in table 1. Transmurally infarcted segments had significantly lower FA (FA subendocardial MI = 0.27 ± 0.04, FA transmural MI = 0.23 ± 0.02, p < 0.01), lower E2A (E2A subendocardial MI = 47 ± 7°, E2A transmural MI = 38 ± 6°, p < 0.01) and lower proportions of right-handed cardiomyocytes (RHM subendocardial MI = 21 ± 5%, RHM transmural MI = 14 ± 5%, p < 0.01) than subendocardial infarct segments.  Conclusion: Compared to subendocardial MI segments, the diffusion of water molecules is more isotropic in transmurally infarcted myocardium as evidenced by lower FA values, signifying increased structural disarray. The significantly lower E2A values suggest that laminar sheetlets of transmural infarct segments remain fixed at shallower angles during systole and are unable to reach their usual contractile configuration. The lower proportions of RHM on HA maps highlight the significantly greater loss of subendocardial cardiomyocytes in transmural infarct segments. Further studies are required to assess if these segmental changes can be predictive of long-term LV remodelling.